Causal Modeling of the Effect of Foreign Direct Investment, Industry Growth and Energy Use to Carbon Dioxide Emissions - Warsono, Warsono; Russel, Edwin; Wamiliana, Wamiliana; Usman, Mustofa; Widiarti, Widiarti; Elfaki, Faiz Ahmed M. (International Journal of Energy Economics and Policy, 2020)
Application of Path Analysis for causal modeling has been widely used in many areas of studies, such as in social science, education, biology, medical, sociology, and economics. In this study, path analysis is applied to test a relationship model among variables: Foreign Direct Investment (FDI), Industry growth (IND), Energy use (ENR), and Carbon dioxide (CO2) emissions. Aims of this study are to know whether there exist direct effect of Foreign Direct Investment (FDI) to Industry growth (IND), direct effect of Foreign Direct Investment (FDI) and Industry growth (IND) to Energy use (ENR), and direct effect of Industry growth (IND) and Energy use (ENR) to Carbon dioxide (CO2) emissions. Results of analysis show that there is a direct effect of Foreign Direct Investment (FDI) to Industry growth (IND) where the effect is determined as 0.3597; parameter estimate is significant and meaningfulness. There is direct effect of Foreign Direct Investment (FDI) and Industry growth (IND) to Energy use (ENR). Effect of Foreign Direct Investment (FDI) to Energy use (ENR) is identified as 0.2736; parameter estimate is not significant, but the value is still meaningfulness. Direct effect of Industry growth (IND) to Energy use (ENR) is -0.4975; parameter estimate is very significant. There is a direct effect of Industry growth (IND) and Energy use (ENR) to Carbon dioxide (CO2) emissions. Effect of Industry growth (IND) to Carbon dioxide (CO2) emissions is 0.0557; parameter estimate is not significant, but the value is still meaningfulness. Direct effect of Energy use (ENR) to Carbon dioxide (CO2) emissions is 0.9597 where parameter estimate is very significant and meaningfulness. Keywords: path analysis, decomposition of correlation, direct effect, indirect effect, total effect JEL Classifications: C51, Q4, Q43 DOI: https://doi.org/10.32479/ijeep.8528